Mkhas maṅ Blo gsal Bye baʼi gliṅ gi thun moṅ ma yin paʼi chos spyod bʼzugs so = Chhos-spyod (Paṇ-chen Bsod-nams-grags-pa literature series, 1979)
Collected rituals and prayers of the Blo-gsal-gliṅ Monastery tradition.